Faktors Which in Fluence the Formation the Company Wage System (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article discusses the factors which affect the pay system. The efficiency of the payment system depends on external and internal factors such as social, economic, legal and political conditions, the company’s strategy, organizational structure and culture, business goals, expectations of the employee, etc.A company’s remuneration policy should meet a policy which is conducted at national and regional level. National and local wage policy implement through economic and financial instruments such as prices, taxes, subsidies, exchange rate policy. A company’s remuneration policy should achieve the company goals. The company activity shows that it should be related to the company development strategy, which increases the effectiveness of its implementation. Also, if the wage system does not meet the business plan goals, for example, when it was stolen from the other company with a different strategy, it would damage the company. In conclusion from the reasons, I have given we need to analyze the development plan regarding of its impact on the pay system.A significant effect on the formation of the wage system has a hierarchal level of the company management and organizational structure of the enterprise as well. Traditional organizational structures have a small degree of elasticity because their structure is based on a direct functional subordination. Organizational interdependence helps relate the salary of the employees and the results of the individual business units. It contributes creating an efficient system of economic stimulation for the staff. Furthermore, a company remuneration policy should be connected with organizational (corporate) culture of thecompany, it will increase its effectiveness. An essential component of organizational (corporate) culture is the company communication system, which helps to link the different levels of the organization, coordinate their activities, improve product quality, customer service, etc. So, the company needs to consider factors which influence the pay system. It helps to transform the enterprise strategic plan into operational actions of employees and promotes the strategy implementation.
Keywords: external and internal factors of the environment, business development strategy, organizational structure, corporate culture, company’s goals, expectations of employees, wage system